LEVERAGING INNOVATIVE MARKETING STRATEGIES IN RETAIL THROUGH DISTRIBUTED DATA AND KNOWLEDGE -BASED SYSTEMS (Marketing Journal, 2025)
In today’s competitive retail landscape, innovative marketing strategies are essential. This paper explores how distributed data systems and knowledge -based technologies can enhance marketing effectiveness. By analyzing data from diverse sources and applyi ng AI -driven insights, retailers can better understand customer behavior and market trends. Knowledge -based systems enable personalized marketing and precise targeting. A distributed approach improves scalability, responsiveness, and security. The paper al so addresses data privacy challenges. In conclusion, leveraging advanced analytics and intelligent systems helps retailers gain a competitive edge and achieve sustainable growth.
Keywords: innovative marketing strategies; retail industry; distributed data; knowledge -based systems; customer engagement; advanced analytics; competitive advantage